Inovasi Kurikulum: Konsep, Karakteristik dan Implementasi Kurikulum Berbasis Komppetensi (KBK) - Dewi Fitriani; Ani Rindiani; Qiqi Yuliati Zaqiah; Mohamad Erihadiana (Jurnal Dirosah Islamiyah, 2022)
Efforts to improve the quality of education by conducting curriculum development are a necessity, because the curriculum is the pillar as well as the direction of the implementation of education in schools. In accordance with global demands when the implementation of AFTA (Asean Free Trade Area) and AFLA (Asean Free Labor Area) the demands of the world of education are increasingly complex. The world of education is required to be able to produce skilled workers who are able to exist and survive in these global developments. because to meet the demands of these developments, improvement and renewal of various components of education, especially the education curriculum, is an urgent thing to do, because in reality the 1994 curriculum is no longer relevant to deliver students to be able to compete with the global development of society, for that the government through the Ministry of National Education in the 2004/2005 academic year introduced a new curriculum called the Competency-Based Curriculum (KBK) with various studies and careful planning. Keywords: Competency-Based Curriculum, life skills, school reform.